Merits and Shortcomings of Heat Flow Estimates from Bottom Simulating Reflectors - Minarwan Minarwan; Rahmat Utomo (Ikatan Ahli Geologi Indonesia, 2015)
The presence of gas hydrates in deep marine sediments and their Bottom Simulating Reflectors (BSRs) on seismic lines can be used to estimate present-day surface heat flow. Despite its limited accuracy, the estimated heat flow is still useful as an input in thermal maturity modeling of a frontier basin.BSRs commonly occur at several hundred meters below the seafloor, in low latitudes generally in areas with water depth greater than about 700-1000m. They run parallel to the sea floor and may cross-cut lithological boundaries. They represent a phase boundary between a gas-hydrates-stable zone and underlying free gas- and water-saturated sediments. Since the depth of the hydrate- free gas phase change is a function of temperature, depth (pressure) and gas composition for a given gas composition (assuming hydrostatic pressure and mainly methane gas), the temperature gradient between seafloor and the BSR can be calculated from its depth. The temperature gradient can then be converted into heat flow, provided that thermal conductivity of the sediment is known.